Utilization of Fly Ash Waste in the Cement Industry and its Environmental Impact: A Review - Ratih Permatasari; Ahyahudin Sodri; Haruki A gustina (Jurnal Penelitian Pendidikan IPA, 2023)
The cement industry is one of the most important industries in the development of a country. However, the production activities of the cement industry also cause significant environmental impacts, one of which is air pollution. One of the by-products of fuel combustion in the cement industry is fly ash, which if not managed properly can pollute the air and the surrounding environment. This research aims to provide an overview of the environmental impacts of using fly ash in the cement industry, especially in relation to air pollution. This research uses the literature review method, which is by collecting and reviewing literature or documents related to the research topic. The data sources used in this research are scientific journals, books, and other related documents. Data analysis in this study was carried out by reviewing and examining literature or documents related to the research topic, then summarizing and compiling the results of the analysis into an overview. Based on the results of this study, it can be concluded that the use of fly ash in the cement industry has significant environmental impacts, especially related to air pollution. However, there are several technologies and fly ash processing methods that can reduce the environmental impact of cement industry production activities, such as the use of fly ash as raw material for making lightweight concrete or as raw material for the production of other building materials.